Risk Allocation In International, European, And Turkish Business Law - Caglar Sahin (Universitas Islam Indonesia, 2023)
There are differences in risk allocation in agreements under the civil law and common law systems. However, similar case law on overseas sales in international business law remain apparent. Therefore, INCOTERMS has a significant impact in this regard. In addition, this effect is sometimes seen in determining the ownership rights as well. The question here is how can the same result from the viewpoint of the passing of risk and property be obtained for all parties in international business law. In this study, the Author used a comparative method by comparing the French, German, Turkish, and English laws, and the United Nations Convention on Contracts for the International Sale of Goods on risk allocation in the sale of goods. Also, case laws were analyzed and compared to find out the main differences in practice. In addition, the effects of the use or absence of INCOTERMS in practice were discussed. As a result, it is better to utilize the Free on Board; and Cost, Insurance and Freight INCOTERMS, as well as the jurisdiction clauses in their contracts for business parties to reach the same result in terms of the passing of risk and property.Keywords: Risk Allocation, Ownership, INCOTERMS. Alokasi Risiko Dalam Hukum Bisnis Internasional, Eropa, Dan Turki AbstrakAda perbedaan dalam alokasi risiko dalam perjanjian di bawah hukum perdata dan sistem hukum umum. Namun, kasus hukum serupa tentang penjualan di luar negeri dalam hukum bisnis internasional tetap terlihat. Oleh karena itu, INCOTERMS memiliki dampak yang signifikan dalam hal ini. Selain itu, efek ini terkadang terlihat dalam menentukan hak kepemilikan juga. Pertanyaannya di sini adalah bagaimana hasil yang sama dari sudut pandang pengalihan risiko dan properti dapat diperoleh untuk semua pihak dalam hukum bisnis internasional. Dalam penelitian ini, Penulis menggunakan metode komparatif dengan membandingkan hukum Perancis, Jerman, Turki, dan Inggris, dan United Nations Convention on Contracts for the International Sale of Goods tentang alokasi risiko dalam penjualan barang. Juga, hukum kasus dianalisis dan dibandingkan untuk mengetahui perbedaan utama dalam praktiknya. Selain itu, efek dari penggunaan atau tidak adanya INCOTERMS dalam praktik juga dibahas. Akibatnya, lebih baik menggunakan Free on Board; dan Biaya, Asuransi dan INCOTERMS Pengangkutan, serta klausul yurisdiksi dalam kontrak mereka untuk pihak bisnis untuk mencapai hasil yang sama dalam hal pengalihan risiko dan properti.Kata kunci: Alokasi Risiko, Kepemilikan, INCOTERMS.